Impact of Early COVID-19 Pandemic on Common Ophthalmic Procedures Volumes: A US Claims-Based Analysis. (2nd November 2022) - Azad, Amee D.; Mishra, Kapil; Lee, Eric B.; Chen, Evan; Nguyen, Alexander; Parikh, Ravi; Mruthyunjaya, Prithvi
ABSTRACT: Purpose: The COVID-19 pandemic has had a profound effect on the delivery of healthcare in the United States and globally. The aim of this study was to evaluate the impact of COVID-19 on common ophthalmic procedure utilization and normalization to pre-pandemic daily rates. Methods: Leveraging a national database, Clinformatics™ DataMart (OptumInsight, Eden Prairie, MN), procedure frequencies and daily averages, defined by Current Procedural Terminology codes, of common elective and non-elective procedures within multiple ophthalmology sub-specialties were calculated. Interrupted time-series analysis with a Poisson regression model and smooth spline functions was used to model trends in pre-COVID-19 (January 1, 2018–February 29, 2020) and COVID-19 (March 1, 2020–June 30, 2020) periods. Results: Of 3, 583, 231 procedures in the study period, 339, 607 occurred during the early COVID-19 time period. Anti-vascular endothelial growth factor injections (44, 412 to 39, 774, RR 1.01, CI 0.99–1.02; p = .212), retinal detachment repairs (1, 290 to 1, 086, RR 1.07, CI 0.99–1.15; p = .103), and glaucoma drainage implants/trabeculectomies (706 to 487, RR 0.93, CI 0.83–1.04; p = .200) remained stable. Cataract surgery (61, 421 to 33, 054, RR 0.77; CI 0.76–0.78; p < .001), laser peripheral iridotomy (1, 875 to 890, RR 0.82, CI 0.76–0.88; p < .001), laser trabeculoplasty (2, 680 to 1, 753, RR 0.79, CI 0.74–0.84; p < .001), and blepharoplasty (1, 522 to 797, RR 0.71, CI 0.66–0.77; p < .001) all declined significantly. All procedures except laser iridotomy returned to pre-COVID19 rates by June 2020. Conclusion: Most ophthalmic procedures that significantly declined during the COVID-19 pandemic were elective procedures. Among these, the majority returned to 2019 daily averages by June 2020.